Analysis of the Kendari City Government Strategy in Maintaining Food Security During the Covid-19 Pandemic - Salam, Yully Angryanthy; Saediman, Haji; Limi, Muhammad Aswar (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2021)
The Covid-19 pandemic that has taken place since December 2019 affects various aspects of socio-economic life, including in the fulfillment of food needs. The research aims to find out the strategic priorities of the Kendari City government in maintaining food security during the Covid-19 Pandemic. The informants were two persons from the offices of Food Security and Agriculture Services at Kendari City government. Data were analyzed using descriptive qualitative analysis. The results showed that the Kendari City government in maintaining food security during the Covid-19 Pandemic took five strategies, namely (i) providing social assistance to affected communities, (ii) guaranteeing food distribution, (iii) monitoring and maintaining inflation rates, (iv) increasing food production, and (v) diversification of food and commodities.